Two media visions, one object of regulation: legitimization for some, criminalization for others: Two media visions, one object of regulation: legitimization for some, criminalization for others - Rodríguez Mera, Andrés (Quórum Académico, 2023)
This article analyzes the organization of the discourse in the news programs -Televistazo and 24 Horas- around the legal and illegal commercialization of non-psychoactive and psychoactive cannabis in Ecuador. Its objective is to explain the media legitimization and criminalization of actors with interests and subjects of rights. From a qualitative methodology, a research corpus is composed from June 2020 to June 2022. In addition, a documentary analysis of two laws and two life stories of illegal cannabis traders are carried out. It is concluded that media criminalization promotes the prosecution and criminalization of consumers and growers more frequently than state control institutions.